Pengaruh Variasi Diameter Pipa Primer Terhadap Pola Resapan Air Irigasi tetes Bertingkat Pada Media Tanam Polybag - Negara, I Dewa Gede Jaya; Hartana, Hartana; Supriyadi, Anid; Suroso, Agus; Julio, Ryan Bagus (LPPM Universitas Mataram, 2024)
Multilevel drip irrigation is an irrigation method that supports water-saving agricultural activities in limited areas by channeling water through perforated pipes from emitters. The ideal multistage drip irrigation system can provide the same drip volume to plants, so the distribution of irrigation water and its depth need to be important factors to pay attention to in order to provide optimal plant irrigation. This research aims to determine the effect of using variations in primary channel pipe diameter on the distribution of drip irrigation and the depth of infiltration of irrigation products in a 3 (three) tier drip irrigation network. Tests were carried out on primary pipes from floors 1 to 3 with a diameter of Â½